Incline Prevention Reinforcement Structure– Controlling Building Incline - Won Song Rim; Song In Chol (International Journal of Architecture and Urbanism, 2022)
By chance facto (disasters, botchery operation) Incline Prevention Reinforcement Structure–Controlling Building Incline is to prevent Building incline when Building incline is measured after Building construction is finished, And is also to prevent Building incline when designs Building. It setted the Incline Prevention Reinforcement plate and pile on building which leans due to plate irregularly distributed sagging to control the deviation, so the range of deviation is under permissible value and it makes building cost save and Building date shortening.